Confessions of a Nielsen household. - Raymondo, James C. (American Demographics, 1997)
The writer discusses his experience of participating in the Nielsen Media Research television ratings system. He notes that Nielsen relies on a sampling strategy known as a “cluster sample,” which is used for most national probability samples in the U.S. and is based on the fact that households are situated in geographic places. He explains that having agreed to participate in the ratings process, a group of Nielsen's technicians visited the writer's home to hook up the monitoring equipment to his TVs and VCRs. He says that Nielsen representatives call each household periodically to ensure that the household information is up to date and to see if there are any difficulties but that there is little financial incentive to be a Nielsen household. He points out that it is not possible to say with certainty what influence his participation in the Nielsen ratings had on television. He concludes that the ratings may be the definitive basis for establishing advertising rates but that television people obviously make decisions based on other considerations.